2005
DOI: 10.1021/bi050297j
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphoserine−Lysine Salt Bridge within an α-Helical Peptide, the Strongest α-Helix Side-Chain Interaction Measured to Date

Abstract: Phosphorylation is ubiquitous in control of protein activity, yet its effects on protein structure are poorly understood. Here we investigate the effect of serine phosphorylation in the interior of an alpha-helix when a salt bridge is present between the phosphate group and a positively charged side chain (in this case lysine) at i,i + 4 spacing. The stabilization of the helix is considerable and can overcome the intrinsically low preference of phosphoserine for the interior of the helix. The effect is pH depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(105 citation statements)
references
References 35 publications
5
100
0
Order By: Relevance
“…[32] It was also demonstrated that phosphorylation of a-helices can be stabilizing, but only with appropriate neighboring residues. [33,34] Although steric bulk is an important factor associated with the changed folding behavior of the PP, our results imply that it is not the essential factor because the much larger sugar moiety does not lead to the same result. Calculated van der Waals volumes of the native and modified serine side-chains show that phosphorylation increases the side-chain volume by a factor of two, whereas incorporation of a single galactose residue results in a six-fold increase in volume (see the Supporting Information).…”
Section: Discussionmentioning
confidence: 60%
“…[32] It was also demonstrated that phosphorylation of a-helices can be stabilizing, but only with appropriate neighboring residues. [33,34] Although steric bulk is an important factor associated with the changed folding behavior of the PP, our results imply that it is not the essential factor because the much larger sugar moiety does not lead to the same result. Calculated van der Waals volumes of the native and modified serine side-chains show that phosphorylation increases the side-chain volume by a factor of two, whereas incorporation of a single galactose residue results in a six-fold increase in volume (see the Supporting Information).…”
Section: Discussionmentioning
confidence: 60%
“…The concentrations of the α-synuclein proteins in the fibrillar solutions were determined via measurements of the tyrosine absorption (extinction coefficient at 280 nm 1209 M −1 cm −1 ) [22].…”
Section: Absorption Measurementsmentioning
confidence: 99%
“…This proposal was also supported from the retention time behavior of ␣-casein N-acetylated phosphopeptides where an increase in retention time was consistently observed upon AP treatment in contrast to the non-derivatized phosphopeptides. In a similar fashion, a few studies have shown that introduction or removal of a phosphate group completely destroys the stability and conformation of the peptide because salt bridges are disrupted from basic or N-terminal residues (32,33). Conformational studies of phosphopeptide secondary interactions are presently in progress to further characterize possible effects that will reveal a more complete reasoning of the model.…”
Section: Discussionmentioning
confidence: 98%
“…Highly sensitive detection techniques are required because phosphoproteins represent only a small proportion of any given cell extracts (typically ϳ1-2%) (4). Most conventional methods such as two-dimensional gels, 32 P radioactive labeling, and Western blotting have limited features, which do not enable them to comprehensively profile phosphoproteome change or identify the exact phosphorylation site.…”
Section: Molecular and Cellular Proteomics 7: 645-660 2008mentioning
confidence: 99%